2021
DOI: 10.1038/s41598-021-95366-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of non-cystic fibrosis bronchiectasis on critically ill patients in Korea: a retrospective observational study

Abstract: This study investigated the impact of bronchiectasis on patients admitted to the intensive care unit (ICU) at a hospital in Korea. Patients with bronchiectasis were diagnosed using results of chest computed tomography performed before ICU admission. The severity of bronchiectasis was based on the number of affected lobes, and patients with ≥ 3 bronchiectatic lobes were classified into the severe bronchiectasis group. Overall, 823 patients were enrolled. The mean age was 66.0 ± 13.9 years, and 63.4% were men. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The multiple Cox regression analysis showed that recurrent hemoptysis was positively correlated with the number of bronchiectatic lobes. A Korean study showed that the number of bronchiectatic lobes was positively related to the in‑hospital mortality, and negatively related to the survival rate [ 34 ]. Efforts should be made to delay the progression of bronchiectatic lobes, especially in patients with hemoptysis.…”
Section: Discussionmentioning
confidence: 99%
“…The multiple Cox regression analysis showed that recurrent hemoptysis was positively correlated with the number of bronchiectatic lobes. A Korean study showed that the number of bronchiectatic lobes was positively related to the in‑hospital mortality, and negatively related to the survival rate [ 34 ]. Efforts should be made to delay the progression of bronchiectatic lobes, especially in patients with hemoptysis.…”
Section: Discussionmentioning
confidence: 99%